Evaluación de la floración de tres clones trinitarios de cacao a nivel de cojín floral, bajo las condiciones climáticas del distrito de Cacatachi – San Martín - Marrero Sánchez, Mery Elizabeth (2009)
With the object to evaluate the behavior the opening and pollination of flowers in three (03) clones of cacao, under the incidence of the humidity and soil temperature, and also determine the behavior of flowering according to the influence of climatic factors as temperature ambient average, precipitation and relative humidity. To realized a study in open-pollinated seedbed of cocoa, located in the District-Cacatachi belonging to the Faculty of Agricultural Sciences, University National of San Martín, put to the test using a stratified systematic design three clones of cocoa ( ICS-1 ICS-95 and CCN - 51), whose evaluation was to determine the number of floral cushions, number of flowers pollinated and the influence of climatic factors on the flowering of a meter branch located in the middle of each branch per plant. The studies reported that the soil temperature for the clones (ICS-1 ICS-95 and CCN-51) above 24 degrees C, decreasing the opening of pollination and floral cushions, and also the effect of soil humidity in the cushions and open pollinated flowers are not so directly linked with each other. On the other hand, considering the rainfall between the 228.40 mm, clones ICS-1 ICS-95 and CCN-51 opening for better pollination and floral cushions, taking risks when the rain fell to 21,90 mm.